Preferensi Mahasiswa terhadap Kajian Keislaman di IAIN Surakarta (Analisis Konjoin terhadap Mata Kuliah Keislaman pada Mata Kuliah Wajib Institut IAIN Surakarta) - Supandi Supandi; Tsalis Muttaqin; Fathan Fathan; Siti Nur Laili Muhadiyatiningsih; Akhmad Anwar Dani (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2017)
This study focuses on student preference for Islamic Subjects contained in the Compulsory Courses Institute at IAIN Surakarta. By using conjoint analysis maps the research institute of the compulsory subjects of the most favored by students and the dominant factor underlying these preferences. The study was conducted on 584 students were selected by stratified random sampling of 8377 active students IAIN Surakarta. Collecting data using the card preference which is based on combination approach full profile attributes of subjects and reasons for choosing subjects.The study concluded that students assume Subjects Sejarah Peradaban Islam as a compulsory subject institute the most preferred with the attribute values of 26.71% and Metodologi Studi Islam became the most disliked by the attribute value 19.18%. While the dominant factor influencing the preference of students to institute compulsory subjects are used instructional media lecturer and desirability level of 22.01%, the quality factor of teaching faculty is the second reason of 21.50%, the lecture method used lecturer at 20.69% , materials and teaching materials are delivered to 18.56%, while 17.24% of the lecture time.